MISOPROSTOL FOR INDUCTION OF LABOR IN TERM PREGNANCY - Permana AW, Gede Angga; Kemara, Putera; Megadhana, I Wayan (E-Jurnal Medika Udayana; vol 3 no 1 (2014):e-jurnal medika udayana, 2014)
Induction of labor refers to the process whereby uterine contractions are initiated by medical or surgical means before the onset of spontaneous labor. Several studies have shown that continuous intravenous infusion of oxytocin is less efficient, particularly when there are unfavorable cervical conditions, leading frequently to a cesarean section, because of induction failure. Misoprostol is a cervical modifying agent and labor inductor. The typical effect of a single dose of oral misoprostol is an increase in uterine tonus. Sustained plasma level of misoprostol is required for the development of regular contractions appear. The bioavailability of vaginal misoprostol also greater compared to oral, sublingual and rectal administration. Using misoprostol for cervical ripening and labor induction represented a 47% reduction in the risk of having a cesarean section ( risk ratio = 0.53 ) . In cases of unfavorable cervix condition, the use of misoprostol could produce several beneficial effects compared to other inductor such as oxytocin
Keywords: misoprostol, labor induction